L’Adversaire d’Emmanuel Carrère : transgressions des limites, limites de la transgression - Romestaing, Alain (Romanica Silesiana)
The Adversary, a narrative by Emmanuel Carrère, based on a sordid and disconcerting true story, revolves around an act of transgression — that of Jean-Claude Romand who, after deceiving his relatives for 18 years into thinking that he was a renowned doctor, killed all his family when the truth about his life was about to come out into the open. Carrère, in identifying Romand with the “Adversary” (i.e. with Satan) proposes a metaphysical, moral, social, as well as literary reading of transgression. The combination of deception with murder not only causes the irruption of evil in apparently peaceful lives, but it also challenges language itself, as well as writing which has to deal with a man both monstrously other and monstrously familiar. So, looking at it more closely, it seems that the explosion of transgression in The Adversary is to be read more as an anxious consciousness of the flimsiness of the boundaries than as the latter being called into question. Key words: Emmanuel Carrère, transgression, evil, identity.